A study of the acquisition practices of the member libraries of Mendiola Consortium - Reside, Pia P.; Faderon, Rosalie B.; Lapuz, Elvira B.; Fonseca, Soledad J. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The Mendiola Consortium is an organization of four institutions located in Mendiola, Manila , Centro Escolar University, College of the Holy Spirit, La Consolacion College, and San Beda College, which have formally agreed to pool their manpower and physical resources to enhance their capability to provide quality education and public service, and to participate more effectively in the attainment of national development goals.
The primary objective of this study was to find out the acquisition practices of the member libraries of the Mendiola Consortium. Forty (40) respondents were requested to answer the questionnaires. Respondents were full-time and regular librarians of the member libraries of the Mendiola Consortium. There was 100 percent rate of returns.
This study utilized the descriptive method of research. Through a descriptive document analysis of the gathered documents, a comparison of the libraries' acquisition policies was also taken into consideration. Interviews were also conducted to ensure valuable information on the problem being investigated.
The respondents' profiles were studied and tabulated. The acquisition practices of the four institutions were also studied and analyzed. The study revealed that they have different written acquisition policies and have similar acquisition practices in acquiring books and other library materials. They acknowledged acquisition planning as an important phase of acquisition work. They acquire books through purchase, gifts/donations and exchange of school publications like journals but not book exchange. The member libraries of the Mendiola Consortium do not practice cooperative acquisition.
The study recommended the following: (1) member libraries of the Mendiola Consortium must be updated with the current practices of the different progressive academic libraries in materials acquisitions, including online ordering, online payment and materials selection; (2) librarians must exert more effort to be able to solicit valuable materials to supplement regular acquisitions; (3) involvement in other consortia or network to add to possible sources of library materials; (4) there must be a review of existing policies and procedures to be able to identify the aspects of acquisition work that are no longer applicable or beneficial to the library; (5) provision for a feedback (evaluation) mechanism to determine effectivity of current acquisition procedures; and (6) the chief librarians should discuss with their respective administrators the advantages that will accrue if they embark on a cooperative acquisitions program. The member institutions, more or less, have started cooperative endeavors in other aspects. Now is the time to think of library cooperation and networking.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Acquisitions (Libraries) -- Philippines -- Manila